Strain Distribution in a Kennedy Class I Implant Assisted Removable Partial Denture under Various Loading Conditions - Reza Shahmiri; John M. Aarts; Vincent Bennani; Raj Das; Michael V. Swain (Hindawi Limited, 2013)
Purpose. This in vitro study investigates how unilateral and bilateral occlusal loads are transferred to an implant assisted removable partial denture (IARPD). Materials and Methods. A duplicate model of a Kennedy class I edentulous mandibular arch was made and then a conventional removable partial denture (RPD) fabricated. Two Straumann implants were placed in the second molar region, and the prosthesis was modified to accommodate implant retained ball attachments. Strain gages were incorporated into the fitting surface of both the framework and acrylic to measure microstrain (μStrain). The IARPD was loaded to 120Ns unilaterally and bilaterally in three different loading positions. Statistical analysis was carried out using SPSS version 18.0 (SPSS, Inc., Chicago, IL, USA) with an alpha level of 0.05 to compare the maximum μStrain values of the different loading conditions. Results. During unilateral and bilateral loading the maximum μStrain was predominantly observed in a buccal direction. As the load was moved anteriorly the μStrain increased in the mesial area. Unilateral loading resulted in a twisting of the structure and generated a strain mismatch between the metal and acrylic surfaces. Conclusions. Unilateral loading created lateral and vertical displacement of the IARPD. The curvature of the dental arch resulted in a twisting action which intensified as the unilateral load was moved anteriorly.